Evaluation Of Dehydration Performance Of Belitung Taro (Xanthosoma Sagittifolium) Using Tray Dryer - Maktum Muharja; Rizki Fitria Darmayanti; Achri Isnan Khamil; Andika Prastika; Muhammad Rizalluddin; Siska Nuri Fadilah; Difka Augustina Diana Sari (IPTEK The Journal for Technology and Science, 2023)
Belitung Taro (Xanthosoma sagittifolium) is a plant that can be processed into various food products. The high-water content of taro and the lack of a precise drying system made this material easy to rot. This study aims to evaluate the dehydration performance of tray dryers to reduce the water content of Belitung Taro. The independent variables used were air velocity (3-6 m/s), taro thickness (1-4 mm), and drying time (30-120 min). The results showed that the optimum drying time of taro is 30 min. The dryer airflow of 5 m/s significantly reduces the water content. The thickness of the slices positively affects the drying rate. The lowest water content was obtained in drying with a thickness of 1 mm. The ANOVA results show the effect of thickness, time, and flow rate variations on the drying rate. Three types of mathematical modeling are used to estimate moisture content: Newton, Page, and Modified Page. The Modified Page equation was preferred to detect the moisture content of the taro. From this study, the optimum condition of the tray dryer can be the best solution to dehydrate Belitung Taro effectively and efficiently